A utilização dos meios de autocomposição como forma de resolução de conflitos nas relações envolvendo o poder público e as organizações econômicas e sociais - Maretti, Luis Marcello Bessa (2021)
This master´s thesis is on the contemporary difficulties and challenges of jurisdictional provision by the Brazilian´s Courts. It aims to demonstrate the positive and negative implications of the use of alternative dispute resolution – ADR mechanisms, involving the Public institutions of the Capital of the State of Paraná and Economic and Social Organizations, when compared with the traditional rules of procedure used by the local Courts. The research carried out was bibliographic, where a survey and a record of the most recent books in the area of self-composition was made; and documentary, opportunity in which the history and the main existing Brazilian law regarding the matter were presented. It was also descriptive, in which the main actions of the federal and local Courts aimed at promoting conflict resolution through mediation were analyzed; and applied, including through case studies and surveys. At this topic, the national indexes of conciliation of the Brazilian´s Courts in recent years were demonstrated; as well as the reality experienced by “Juizados Especiais da Fazenda Pública de Curitiba” (specialized local Courts on small claims involving public institutions) in the years of 2018 and 2019. As a result, it was concluded that, despite the existence of a rich doctrine regarding alternative dispute resolution mechanisms, as well as numerous normative acts aiming at the adoption of them, in the day-to-day of jurisdiction provision, this scenario was not reflected; bearing in mind, few cases were resolved by mediation. The failure in the use of this technology, among other factors, could be extracted from the reality presented by these specialized local Courts, whose case management measures, and the behavior of the actors (plaintiff and defendant); remained focused on the use of the traditional rules of procedure. This fact only demonstrate that changing the procedure is not enough when the formalist mentality of the nineteenth century is still present. Only by overcoming this winner-loser logic will it be possible to stop the current justice crisis.